2006
DOI: 10.1080/10284150600621964
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate concentration in whole saliva and taste responses to monosodium glutamate in humans

Abstract: It is universally accepted that saliva plays an important role in taste sensations. However, interactions between constituents of whole saliva and the five basic taste modalities are still poorly understood. The aim of the present study was to evaluate possible relationship between endogenous glutamate (Glu) levels in whole saliva and taste responses to a prototypic umami substance, monosodium glutamate (MSG; 0.03-10.0%). Rated intensity and pleasantness of MSG taste was studied in healthy volunteers divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
2
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 33 publications
1
20
2
2
Order By: Relevance
“…Baseline salivary concentrations of glutamate remained constant and were not different between the MSG and placebo sessions. These concentrations are similar to a previous study that reported mean saliva concentrations of glutamate of 18±1 μM in 18 subjects [20]. However, administration of MSG tended to increase salivary glutamate concentration each day, which suggests the potential that accumulation might have been occurring.…”
Section: Discussionsupporting
confidence: 90%
“…Baseline salivary concentrations of glutamate remained constant and were not different between the MSG and placebo sessions. These concentrations are similar to a previous study that reported mean saliva concentrations of glutamate of 18±1 μM in 18 subjects [20]. However, administration of MSG tended to increase salivary glutamate concentration each day, which suggests the potential that accumulation might have been occurring.…”
Section: Discussionsupporting
confidence: 90%
“…On the receptor level, T1R1-T1R3 are responsible for the taste of umami (Galindo-Cuspinera & Breslin, 2006). Reactions to the umami taste have been described as neutral or pleasant (Nicklaus et al, 2005;Scinska-Bienkowska et al, 2006). It has further been found that the taste of IMP is probably caused by glutamic acid in saliva, since IMP itself has no umami taste (Yamaguchi, 1991).…”
Section: Umami Tastementioning
confidence: 96%
“…Salivary glutamate is a possible component to modify the sensitivity of the taste receptor, although its concentration is far lower than the concentration necessary for the detection of its taste in humans (54). The taste of glutamate is recognized to be a basic taste, called ‘umami’, in addition to the basic four taste qualities (sweet, sour, salty and bitter).…”
Section: Effects Of Salivary Secretion On Tastementioning
confidence: 99%